The Effect of Safety Climate on Safety Performance Within Drilling Operation Workgroup in Company Z In Indonesia - Muhammad Dahnil Maulana; Osly. Usman (Cakrawala Repositori IMWI, 2024)
Drilling is one of activities in Upstream O&G Industry which possess high cost and high risk. In 2022, drilling activities contributed to 27% of accidents in upstream O&G operations worldwide. At the early 2023, there had been an increase of work-related accident in drilling operation Region A of Company Z in Indonesia, including accident with fatality consequences. This condition indicated a decline in safety performance in the company. Based on the investigation result, it was shown that “Human Factors” as one of the main root causes. Safety climate can be used to determine individual perceptions in motivating workers to perform their job by prioritizing safety. This study analyses factors contribute to Safety Climate based on NOSACQ-50, namely Management Safety Priority, Commitment, and Competence (MP), Management Safety Empowerment (ME), Management Safety Justice (MJ), Worker’s Safety Commitment (WC), Worker’s Safety Priority and Risk Non-acceptance (WP), Safety Communication, Learning, and Trust in Co-worker Safety Competence (SC), and Worker’s Trust in the Efficacy of Safety System (WT), and their relationship with Safety Performance (SP) within Drilling Operation Workers in Company Z Regional A, specifically in Area 1. Data collected through questionnaires and analysed with SEM Method. The result shows that safety climate aspects concerning conditions at management (MP, ME, and MJ) have indirect relationship to SP. Meanwhile safety climate aspects concerning conditions within workgroup (WC, SC, and WT) have direct and positive relationship to SP, except on WT which has indirect relationship as well to SP. This anomaly could be related with the condition of WP within workgroup which show the weakest safety concern compare to other aspect. This study provides an overview of Safety Climate condition in Company Z Regional A Area 1. Feedbacks are also given to the management as an intervening option to improve safety aspect in the company.